Comparison Of Health Service Utilization by BPJS Participation Status In Brebes - Dhea Salsadilla Kharisma Putri; Bambang Budi Raharjo (Faculty of Medicine, 2026)
ABSTRACTHealth service utilization is an indicator in assessing the success of the healthcare system and equitable access to healthcare services in a country. Differences in socioeconomic status between Contribution Assistance Recipients (PBI) and Non-PBI participants are assumed to influence healthcare utilization patterns. This study aimed to analyze differences in health service utilization based on BPJS participation status at primary healthcare facilities in Brebes Regency, Central Java. This study used a cross-sectional quantitative study conducted at primary healthcare facilities in Brebes Regency, Central Java, Indonesia. The cross-sectional study was conducted from January to February 2026. The sample was selected using a disproportionate stratified random sampling approach supported by Slovin's method. A total of 100 respondents were selected, divided into 50 PBI participants and 50 non-PBI participants. Data were analyzed using univariate analysis and the Mann–Whitney U test.The majority of respondents demonstrated high health service utilization, accounting for 81.0% of the total respondents. The mean rank of health service utilization among PBI participants was 51.51, while among Non-PBI participants it was 49.49. The Mann–Whitney U test showed that there was no statistically significant difference in health service utilization between PBI and Non-PBI participants (U=1199.500; Z=-0.349; p=0.727).There was no significant difference in health service utilization based on BPJS participation status at primary healthcare facilities in Brebes Regency. Implementation of the BPJS Health program has relatively supported equitable access to primary healthcare services among PBI and Non-PBI participants